Reintroduction of Odor Combined with Cognitive Stimulation Supports Creative Ideation via Memory Retrieval Mechanisms. Issue 3 (3rd July 2019) - Akben, Cantürk; Coskun, Hamit
Abstract : Brainstorming is a widely used method for generating creative ideas. There is an interest in various techniques contributing to it; nevertheless, research examining the influence of an aromatic odor as a facilitator has been scarce. Two experiments were conducted for this purpose. In Experiment I, a mandarin odor was presented with either stimulating (relevant) or non-stimulating (irrelevant) words prior to the brainstorming session, then re-presented during it. The findings showed that re-presenting the odor during brainstorming increased flexible and unique ideas through retrieval of stimulating words from memory. Flexibility also played a mediator role between mandarin odor and unique ideas. In Experiment II, odor presentation times were changed. It was presented prior to brainstorming, during it or both. The first odor presentation enhanced idea generation only when there was a second odor presentation. The findings suggested that it was the combination of the odors, presented before (and alongside a list of stimulating words) and during brainstorming, that contributed to the use of stimulating words during brainstorming. These two experiments revealed the role of mandarin odor on flexible thinking and idea generation via memory retrieval. Moreover, the odor increased recalling performance, even when the stimuli were given implicitly and recently learned.